Sweden : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2004)
The Selected Issues paper analyzes tax policy trends at the local level in Sweden and assesses the effectiveness of the vertical fiscal policy coordination system. The study reviews Sweden's local public finances from an international perspective and empirically explores various explanations for the gradual increase in local tax rates. It discusses long-term challenges for local public finances and aggregate fiscal policy coordination. The design of vertical fiscal policy coordination in other countries is described. The paper also examines the Swedish experience of work absence in a European context.